The Relationship between Spiritual Well-Being and Anxiety Levels in Patients in the ICU at Hospital X in 2024 - Widdy Meilania Feron; Feri Agustriyani; Didi Suswanto; Giri Susanto (Journal of Nursing Invention)
Background: When a patient walks into an ICU room, it can be a very stressful moment and cause anxiety. A spiritual approach that aims can alleviate psychological problems and improve the patient's ability to cope with them emotionally and reduce anxiety. Spiritual well-being is a state in which a person feels they have meaning, purpose, and peace in their lives, often related to spiritual or religious aspects.